Explaining the recent reduction of Indonesia's deforestation - Arild Angelsen; Ahmad Dermawan; Malte Ladewig (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2025)
Deforestation in Indonesia has declined sharply since 2015-2016. We use a combination of spatial land use change data, interviews with stakeholders and statistical analysis to explain this reduction. The exact extent of the reduction in deforestation depends on the data set used, and the years or time periods compared, varying between 40% and 90%. A robust estimate is that deforestation has fallen by at least 50% since ca. 2016. The decline is uneven across islands and provinces. The two main "deforestation islands" Kalimantan and Sumatra experienced a major decline, with a relatively larger decline in the former. The provinces with the largest absolute decline were Riau, South Sumatra and Central Kalimantan, followed by West and East Kalimantan. In terms of commodities driving deforestation ("direct drivers"), palm oil is still the most important commodity (46% for 2018-2022, according to MapBiomas Indonesia data, compared to 55% for the period 2010-2017). Pulp is on the rise as a deforestation driver, particularly in Kalimantan. In the three high deforestation provinces on that island, the demand for pulp was behind almost 1/3 of the natural forest conversion in 2022. Mining for coal and valuable minerals such as nickel is also on the rise, with MBI data suggesting its share of national deforestation being 5.4% (2021-2022), compared to less than one (0.9%) for the 2010-2017 period. Mining is particularly important in Sulawesi, where it according to one estimate accounted for 30% of the deforestation in 2021-2022. Five hypotheses are put forward to explain the reduction, related to public policies, private (corporate) policies, civil society pressure, commodity prices, and forest scarcity. (...) While we conclude that all five hypotheses put forward are relevant to explain the recent decline in deforestation, we tentative conclude that public polices - in combination with a forest transition (scarcity) effect - has been the most important factors. Private policies show more mixed results. Behind the public and private policy changes, civil society has played a key role in policy reforms and in promoting more effective implementation though its watchdog role. Non-increasing agricultural commodity prices have made the implementation of forest conservation policies less costly. Deforestation is still a profitable activity for land users and (sub)national governments, and forest conservation is a continuous battle, with future challenges emerging: the effectiveness of current policies may weakened over time, political priorities may change, prices of deforestation-risk commodities may rise, and the composition of direct drivers change - requiring a shift in the policy focus.
hdl:11250/3176540
Keywords: 330